A Model for Specification and Communication of Data for Distributed Multimedia Systems - Son, Sang; Agarwal, Nipun (University of Virginia, Department of Computer Science, 1994)
As network technology provides the capability to handle multimedia traffic and the demand of multimedia services increases, protocols are required for effective communication of multimedia data in a distributed environment. Synchronization is one of the key issues in a multimedia system. Most of the current approaches do not support an integrated solution to the problem of synchronization. In this paper we propose a mechanism for synchronization of multimedia data in distributed environment where the accuracy of the protocol can be tailored to the application. The system model supports live and video-on-demand service. We present a scheme where the specification of the temporal requirements provided by the application can be directly mapped to obtain the information necessary to enforce the synchronization required. We present two examples of specifying the temporal requirements and process of obtaining the information and present performance results of our simulation studies. Note: Abstract extracted from PDF text
Original submission date: 2013-10-10T20:58:33Z